Benchmarking the Egyptian Shopping Tourism Sector against International Best Practices in Dubai, UAE - AbuElEnain, EmadEddin; Dr. Saber Yahia (European Journal of Multidisciplinary Studies, 2017)
Shopping tourism has become one of the main economic motivators for tourism development in several destinations. “Shopping means entertainment and experience. Regardless of trip purpose –business, family or vacation—shopping is woven into the human interactions of the visit.” It means exploring and discovering and could be about the planned or temporary consumption. Shopping became gradually more significant element of the tourism “value chain”. Shopping has improved into a contributing factor determining tourism destination selection, a vital element of the total tourist knowledge and, sometimes, the major tourism incentive. Destinations have consequently an enormous chance to influence this innovative “market trend” by increasing realistic and exclusive shopping experiences that enhance value to their tourist deal while strengthening, and even, outlining their tourism brand and planning. This research suggests that there are increasing numbers of tourists who are travelling to Dubai with the aim of shopping, not only because they are encouraged by a mixture of first-class shopping, reasonable costs, trustworthy deals, Duty-free and a variation of rate or goods related aspects, but the charm of the destination certainly creates decision when selecting a destination. This study provides an outline of the significance and up-to-date types of shopping tourism, principally in the emerging market of Dubai, offering recommendations to support Egypt as a central tourist destination to stimulate the inbound shopping tourism. This research first examines relevant literature on possibility to develop this tourism type in Egypt and make it one of the tourist attractions by comparing it to Dubai, UAE as a shopping destination. The study explores the objectives, and factors affecting the progress of that type in Egypt and the improvements made in Dubai. The research then investigates potentialities of developing that type in Egypt and its impacts on improving the tourist experience in Egypt and increasing the tourist flow into Egypt. Results indicated that shopping tourism could face several obstacles in practical performance, but it could be very helpful in supporting the tourism industry in Egypt especially at the time of deterioration. However, shopping tourism can also offer incentives to the tourism employees who have almost lost their jobs and may change their career. Benefits are not only confined to this, but also extended to cover enhancing existing tourism types and introducing new ones as well as enhancing the tourist numbers and their average expenditure. The Research provides recommendations for actions that could encourage more tourists to visit Egypt as a shopping destination.Keywords: shopping, Dubai, purchasing, goods, products.